Geometrical framework for robust portfolio optimization - Pavel Bazovkin (University of Cologne, Institute of Econometrics and Statistics, 2014)
We consider a vector-valued multivariate risk measure that depends on the user's profile given by the user's utility. It is constructed on the basis of weighted-mean trimmed regions and represents the solution of an optimization problem. The key feature of this measure is convexity. We apply the measure to the portfolio selection problem, employing different measures of performance as objective functions in a common geometrical framework.
Keywords: 330; Multivariate risk measure; robust portfolio optimization; weighted-mean trimmed regions; data central regions; convex risk measure; distortion risk measure